(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
Personal and individual approaches answer the question of what to develop. The answer to this question can be formulated as follows: it is necessary to develop and form not a single set of qualities oriented towards state interests that constitutes an abstract "graduate model", but to identify and develop the individual abilities and inclinations of the student. This is an ideal, but it must be remembered that education should take into account both individual abilities and inclinations, and the social order for the production of specialists and citizens. Therefore, it is more expedient to formulate the task of the school as follows: the development of individuality, taking into account social requirements and requests for the development of its qualities, which presupposes an essentially socio-personal, or rather, a cultural-personal model of education orientation. The following article is devoted to the importance of the above-mentioned approach for the effectiveness of learning